2008
DOI: 10.1007/s00128-008-9437-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pentachlorophenol Degrading Bacterial Consortium from Chemostat

Abstract: A microbial consortium was developed by continuous enrichment of bacterial population isolated from sediment core of pulp and paper mill effluent in mineral salts medium (MSM) supplemented with pentachlorophenol (PCP) as sole source of carbon and energy in the chemostat. The enriched consortium contained three bacterial strains identified as Escherichia coli (PCP1), Pseudomonas aeruginosa (PCP2) and Acinetobacter sp. (PCP3) by morphological and biochemical tests, further confirmation was done using 16S rDNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The initial pyridine concentration of the sample without glucose was lower than the sample with glucose possibly because of preferential utilization of glucose by strain KT-5. Rhee et al [17], Xiong et al [18], Quan et al [20], Yang et al [22] and Sharma and Thakur [23] demonstrated the same results, however, Kao et al [21] suggested extra glucose did not stimulate biodegradation of pentachlorophenol by a pentachlorophenol-degrading strain Pseudomonas mendocina NSYSU.…”
Section: Effect Of Extra Carbon Sourcesupporting
confidence: 47%
See 1 more Smart Citation
“…The initial pyridine concentration of the sample without glucose was lower than the sample with glucose possibly because of preferential utilization of glucose by strain KT-5. Rhee et al [17], Xiong et al [18], Quan et al [20], Yang et al [22] and Sharma and Thakur [23] demonstrated the same results, however, Kao et al [21] suggested extra glucose did not stimulate biodegradation of pentachlorophenol by a pentachlorophenol-degrading strain Pseudomonas mendocina NSYSU.…”
Section: Effect Of Extra Carbon Sourcesupporting
confidence: 47%
“…However, the reverse consequences had been also reported [18,[20][21][22][23]. Consequently, effect of the three substrates on pyridine biodegradation by strain KT-5 was still investigated.…”
Section: Effect Of Different Co-substrates On Pyridine Biodegradationmentioning
confidence: 97%
“…Investigation of the biodegradation of refractory pollutants in the presence of accessible carbon and nitrogen sources might aid in reducing the toxic and growth-inhibiting effects of xenobiotics on cells, thereby increasing the transformation rates of xenobiotics [36]–[38]. However, the reverse consequences had been also reported [39][42]. Consequently, effect of the two substrates on acetamiprid biodegradation by strainD-12 was still investigated.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that Acinetobacter might play a critical role in PCP degradation in paddy soils. Members of Acinetobacter have been defined as PCP degraders (Stanlake and Finn 1982;Sharma and Thakur 2008;Sharma et al 2009), they have the ability to utilize PCP through an oxidative route with ortho ring-cleavage by producing intermediate products like 2,3,5,6-tetrachlorohydroquinone (TCHQ) and 2-chloro-1,4-benzenediol (DCBE) (Sharma and Thakur 2008;Sharma et al 2009). Interestingly, in this study, we found that the primary intermediates of reductive degradation of PCP were TeCP and TCP in the anaerobic reactors, suggesting the possibility that Acinetobacter was able to degrade PCP through the reductive route when presented in the soilmicrobe complex.…”
Section: Microbial Community Shifts Corresponded With Pcp Degradationmentioning
confidence: 99%